Arbitrary motion Synthetic Aperture Radar - Alberius,Filip; Rolander,Erik (Master’s Theses in Mathematical Sciences, 2023)
The purpose of this thesis is to develop a novel approach to producing Synthetic Aperture Radar (SAR) images, assuming the scenario of arbitrary motion in regards to the radar sensor. SAR is a well-researched method for creating 2- or 3-dimensional radar images, traditionally assuming the radar sensor's motion to be linear and highly predictable. Thus the locations where each radar data is sampled are known and follow a predefined pattern. This thesis, however, explores new methods that enable the radar to move freely. We have developed a prototype based on the A121 Pulsed Coherent Radar sensor from Acconeer to demonstrate the performance and use-case potential of the method we came up with. The resulting system can successfully create an accurate map of its surroundings, detecting obstacles in 3D space. Using this prototype setup, we have evaluated different configurations and kinds of optimizations for the algorithm developed, as well as configurations for the radar sensor, including lens choice. We have tested the setup for many different potential targets and evaluated its performance in several different environments. The system relies on a stream of accurate pose data in regard to the radar sensor. Two different systems were explored for this purpose. Firstly, the use of an Inertial Measurement Unit (IMU), and secondly, using the IR lighthouse tracking from virtual reality hardware. Early experiments showed less than promising results for IMU-based tracking, and this path was not deemed worth exploring further. Tracking the sensor using a VR setup, however, showed promising results and more experiments were performed to evaluate the viability and limitations of its use in creating radar images. These two approaches, though, are a subset of a vast number of potential pose-tracking systems. The final results show that SAR is possible to implement in cases where the motion of the radar is arbitrary, given the position of the sensor can be determined to some degree of accuracy for all collected radar data points. It also demonstrates how arbitrary motion SAR could potentially enable more use cases for radar sensors, for example, in VR, robotics for the mapping of environments, and object detection.
Keywords: RADAR; SAR; Synthetic Aperture Radar; Pulsed Coherent Radar; PCR; VR; Virtual Reality; IMU; Inertial Measurment Unit; VAA; Virtual Antenna Array; Obstacle detection; Signal Processing; Matched Filter Method.